IMPLEMENTASI PEMBELAJARAN MENDALAM BERBASIS DIGITAL: STUDI KASUS TERHADAP PEMAHAMAN DAN MOTIVASI BELAJAR PADA MATERI PECAHAN SISWA KELAS V DI SD NEGERI KALIURANG 1 - Ratih Widya Utami; Azamul Fadhly Noor Muhammad; Sulastri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study examines the effectiveness of digital-based deep learning in improving conceptual understanding and learning motivation for fraction topics among fifth-grade elementary students. Using a mixed methods sequential explanatory design with 28 purposively sampled students, the results show significant improvement: learning mastery increased from 25% (pre-test) to 85.7% (post-test), and students' intrinsic motivation shifted from moderate to high. The findings prove that integrating interactive digital media with meaningful pedagogical design effectively facilitates understanding of abstract concepts and fosters student engagement, offering a promising alternative strategy for elementary mathematics instruction.